A evolução do Programa Pró-Equidade de Gênero: 2005-2013 - Bello, Andrea Rosa (2014)
The sexual division of labor is something that still prevails in the labor market and in organizations. The difference between male and female earnings for similar positions, men’s presence in the majority of leadership and decision-making positions, women’s poverty related to lack of access to health and education, are some factors that justify the importance of women’s political empowerment. In this regard, since 2005, the Programa Pró-Equidade de Gênero e Raça (Gender and Race Pro-Equality Program) has been implemented by the Secretaria de Políticas para Mulheres (Secretariat for Women’s Policies), whose main objective is to combat inequalities between genders and races, promoting good practices in workplace in public and private organizations. This research discusses briefly the evolution of this program by means of awarding the Selo Pró-Equidade (Pro-Equality Seal) to public and private organizations in the period of 2005-2013.